Incentive contracts crowd out voluntary cooperation: Evidence from gift-exchange experiments - Simon Gächter; Esther Kaiser; Manfred Königstein (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2024)
Explicit and implicit incentives and opportunities for mutually beneficial voluntary cooperation co-exist in many contractual relationships. In a series of eight laboratory gift-exchange experiments, we show that incentive contracts can lead to crowding out of voluntary cooperation even after incentives have been abolished. This crowding out occurs also in repeated relationships, which otherwise strongly increase effort compared to one-shot interactions. Using a unified econometric framework, we unpack these results as a function of positive and negative reciprocity, as well as the principals' wage offer and the incentive-compatibility of the contract. Crowding out is mostly due to reduced wages and not a change in reciprocal wage-effort relationships. Our systematic analysis also replicates established results on gift exchange, incentives, and crowding out of voluntary cooperation while exposed to incentives. Overall, our findings show that the behavioral consequences of explicit incentives strongly depend on the features of the situation in which they are embedded.
Keywords: C70; C90; 330; principal-agent games; gift-exchange experiments; incomplete contracts; explicit incentives; implicit incentives; repeated games; crowding out